2023
DOI: 10.1108/jkm-04-2022-0325
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management in SMEs: a follow-up literature review

Abstract: Purpose The purpose of this paper is to structure existing research on knowledge management (KM) in small- and medium-sized enterprises (SMEs) to offer a comprehensive overview of research strands and topics in KM in SMEs to determine their evolution over time. Design/methodology/approach The paper, which is considered a follow-up literature review, is based on a systematic literature review that covers 180 scientific papers that were published since the review paper by Durst and Edvardsson in 2012 that cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 215 publications
(335 reference statements)
0
5
0
Order By: Relevance
“…Incorporating KM as a mediator in the model, particularly in the context of SMEs in the manufacturing sector of a developing country, advances our understanding by providing critical empirical insights that can assist SME owners and managers in evaluating the impact of ECs on SP. While McAdam and Reid (2001) posited that KM primarily evolved for large organizations, Durst et al (2023) indicated that KM has recently found its place in various types of organizations, including SMEs. These organizations are encountering novel challenges such as transboundary crises, exemplified by threats that effortlessly transcend geographical and policy boundaries, as seen in events like COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating KM as a mediator in the model, particularly in the context of SMEs in the manufacturing sector of a developing country, advances our understanding by providing critical empirical insights that can assist SME owners and managers in evaluating the impact of ECs on SP. While McAdam and Reid (2001) posited that KM primarily evolved for large organizations, Durst et al (2023) indicated that KM has recently found its place in various types of organizations, including SMEs. These organizations are encountering novel challenges such as transboundary crises, exemplified by threats that effortlessly transcend geographical and policy boundaries, as seen in events like COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…These organizations are encountering novel challenges such as transboundary crises, exemplified by threats that effortlessly transcend geographical and policy boundaries, as seen in events like COVID-19. These crises not only underscore the heightened significance of KM but also demand a fresh comprehension of knowledge resources, possibly necessitating a redefinition (Durst et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge management capabilities, which have fundamentally dynamic characteristics, have a positive impact on product/process innovation by capturing necessary knowledge from a firm's internal and external sources and converting it into productive outcomes [41,42]. Knowledge management can promote the creation of new ideas and ultimately improve R&D performance by facilitating the exchange and sharing of knowledge necessary for R&D [43]. Dynamic knowledge management capabilities interact closely with the learning process and play an important role in internalizing new knowledge obtained through R&D [44].…”
Section: B Randd Failure and Survival Of Smesmentioning
confidence: 99%
“…This study will look into the relationship between an organization’s learning culture and SCR and supplier trust’s role in that relationship before and during a pandemic. Durst et al (2023) provided a framework for understanding the development of KM practices in SMEs by reviewing the various research streams and subjects in this area. Ting et al (2021) investigated the effect of KM on a firm’s innovative performance and the moderating effect of transformational leadership on this connection.…”
Section: Introductionmentioning
confidence: 99%